2020
DOI: 10.1002/jemt.23527
|View full text |Cite
|
Sign up to set email alerts
|

Spore morphology and leaf epidermal anatomy as a taxonomic source in the identification of Asplenium species from Malakand division Pakistan

Abstract: Several studies have demonstrated the usefulness of leaf epidermal, and spore morphological characters in the taxonomy of genus Asplenium. However, works on the Pakistani species of Asplenium are not existent. With the objective to verify the efficacy of leaf epidermal and spore morphological traits, the leaf epidermis and spore morphology in nine Asplenium species occurring in Malakand division was studied. The spores were studied under light microscope (LM) and scanning electron microscope (SEM), whereas for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 60 publications
7
13
0
Order By: Relevance
“…fontanum subsp. pseudofontanum was monolete having bilateral symmetry, distal view was spheroidal, proximal view ellipsoidal, average spores size were 31–36 × 36–42 μm; perispore surface with costate‐alate fold type; anomofenestrate fenestration; reticulate, echinate ornamentation, and with lophate pattern; that agreed with the earlier study (Morbelli & Giudice, 2005; Nayar & Devi, 1964; Shah et al, 2020); while Nayar and Devi (1964) documented spore size 26–30 × 30–34 μm; Shah et al (2020) reported spore size 40.7–55.7 × 30.3–50.4 μm. The spores of A .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…fontanum subsp. pseudofontanum was monolete having bilateral symmetry, distal view was spheroidal, proximal view ellipsoidal, average spores size were 31–36 × 36–42 μm; perispore surface with costate‐alate fold type; anomofenestrate fenestration; reticulate, echinate ornamentation, and with lophate pattern; that agreed with the earlier study (Morbelli & Giudice, 2005; Nayar & Devi, 1964; Shah et al, 2020); while Nayar and Devi (1964) documented spore size 26–30 × 30–34 μm; Shah et al (2020) reported spore size 40.7–55.7 × 30.3–50.4 μm. The spores of A .…”
Section: Discussionsupporting
confidence: 90%
“…trichomanes subsp. quadrivalense was monolete having bilateral symmetry; distal and proximal view was ellipsoidal, spheroidal; average spore size were 31–35 × 36–42 μm; perispore surface with arelofenestrate fenestration; costate‐alate fold type; veined ornamentation and with lophate pattern; that agreed with the earlier study of Lashin (2012); Nayar and Devi (1964); while Shah et al (2020) documented spore size 30.2–50.9 × 30.8–45.5 μm. The spores of A .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Specimens (flowering plants) were identified with the help of native flora (flora of Pakistan) and other available literature Nasir 1989-1991;Nasir 1991-1993;Ali and Qaiser 1986;Qaiser 1993-2017;Qaiser 2000-2012;Ali 1978;Ali 1980;Ali et al 2001;Cronquist 1968;Nasir 1981;Stewart 1967;Stewart 1972), grasses identified with the manual of (Cope 1982;Ahmad et al 1958). Fern and their allies (Pteridophytes) was identified from (Gul et al 2017;Lellinger 2002;Nakaike and Malik 1992;Nakaike and Malik 1993;Nayar 1964;Stewart 1957), flora of China (Zhang et al 2013) and other available literature (Beddome 1866;Beddome 1873;Clarke 1973;Fraser-Jenkins 2014;Hope 1899Hope -1902Shah et al 2020Shah et al , 2021. Plant samples were also confirmed from snapshots existing on the international herbaria website.…”
Section: Plant Preservation and Identificationmentioning
confidence: 82%
“…The anthers were crushed and treated with acetic acid to release the pollen material from it. For staining glycerin jelly was used (Ahmed et al, 2019; Ashfaq et al, 2018; Shah et al, 2020; Zafar et al, 2019; Zafar et al, 2020). The prepared pollen slides were observed under light microscope and photographs were taken at 40× magnification under Nikon FX‐35 Camera equipped with photomicrograph system.…”
Section: Methodsmentioning
confidence: 99%